Behaviors of children with autism before, during and after full moon: A case study - Dizon, Edgar S. (Animo Repository, 2005)
This study aimed to determine the veracity about the claims of many professionals and paraprofessionals about full moon effects on human behavior. It aimed primarily to find out whether full moon influences the frequency of manifestation of maladaptive behaviors of children with autism. Five children with autism were selected as participants of the study. They were pupils of special education in Binan Elementary School in Binan, Laguna. Their ages range from 9 to 18 and had been in this special school for three months. Observations and interview schedules with parents, caregivers, teachers, and other significant people were utilized to determine the following: (1) common, uncommon and unique maladaptive behaviors of the participants, (2) changes, in terms of frequency, in each maladaptive behavior during full moon as compared before and after; and (3) environmental factors affecting the behaviors before, during and after three onsets of full moon. Results gathered indicated that the participants exhibited common and unique maladaptive behaviors. There was no uncommon behavior observed during the onsets of three full moons. All maladaptive behaviors were observed before, during, and after full moon. In terms of changes in the frequency of manifestation, there was no observed pattern of increase in each maladaptive behavior during full moon as compared before and after except for body rocking. In addition, physical, social and biological factors were identified to affect the manifestation of maladaptive behaviors and nonverbal autistic children were more likely to manifest more maladaptive behaviors than the verbal ones.